Indonesia Kanada Dorong Akselerasi Kerjasama Ekonomi - Nazwa Thalifa; Nathalia Josephin Valerie Damanik; Tamaulina Br.Sembiring (Jurnal Multidisiplin Indonesia, 2024)
This research phenomenon revolves around new dynamics in economic relations between Indonesia and Canada, which are characterized by various initiatives to accelerate economic cooperation amidst global and regional challenges. Increasing investment interest, trade diversification and technological cooperation are the main focuses in this discussion. The aim of this research is to analyze the efforts and steps that have been taken by the two countries to increase economic cooperation, as well as identify strategic sectors that can be strengthened for the partnership between the two countries. The results of the discussion show that both countries have taken serious steps to identify obstacles and opportunities in trade and investment. This includes negotiations to strengthen relations through comprehensive trade agreements and increased bilateral business dialogue interactions. Sectorally, renewable energy, mining and education are areas with high potential for collaboration. Apart from that, commitment to sustainable business practices and empowering SMEs are topics that also receive attention. The conclusion of this research shows that accelerated economic cooperation between Indonesia and Canada has positive prospects and can provide mutual benefits. Strategic collaboration between the two countries is needed to face global challenges, such as climate change and economic uncertainty, as well as take advantage of opportunities that arise from the dynamics of the world economy which continues to develop. Increasing communication and understanding of each other's economic policies will be the key to increasing sustainable economic cooperation.